Knowledge and context in Tibetan medicine - McGrath, William A. (Brill, 2019)
Knowledge and Context in Tibetan Medicine is a collection of ten essays in which a team of international scholars describe and interpret Tibetan medical knowledge. With subjects ranging from the relationship between Tibetan and Greco-Arab conceptions of the bodily humors, to the rebranding of Tibetan precious pills for cross-cultural consumption in the People's Republic of China, each chapter explores representations and transformations of medical concepts across different historical, cultural, and/or intellectual contexts. Taken together this volume offers new perspectives on both well-known Tibetan medical texts and previously unstudied sources, blazing new trails and expanding the scope of the academic study of Tibetan medicine. Contributors include: Henk W.A. Blezer, Yang Ga, Tony Chui, Katharina Sabernig, Tawni Tidwell, Tsering Samdrup, Carmen Simioli, William A. McGrath, Susannah Deane and Barbara Gerke.
Keywords: Medicine, Tibetan.; Medicine, Tibetan -- History.; Médecine tibétaine.; Médecine tibétaine -- Histoire.; Medicine, Tibetan; History